Title Nau: The Impact of Title IX on Women's Education in the U.S. and What it Means for India. Issue 2 (2016) - Adams, Taylor; Zhang, Zihe; Holmes, Rebecca; Shah, Pratik
This research investigates the impact of Title IX on women's education in the U.S. and how a comparable policy in India could improve women's education in India. The existing education policies in the U.S. and India were thoroughly reviewed to understand the impact of Title IX on female education over the past 40 years and to recognize gaps in Indian policy. Data from the U.S. Census Bureau, NSF through WebCASPAR and the India Ministry of Human Resource Development was reviewed through descriptive analysis. Different variables from primary, secondary and tertiary education were examined. It was determined that Title IX improved the outcomes for nearly all the markers for female education within the U.S. Thus, the research concluded that despite differences between the educational frameworks of both countries, a form of Title IX policy in India would be beneficial in reducing the gender inequality present in the education system.